Radio detection of colliding wind binaries - Benaglia, Paula (2006)
Four massive, early-type stars, three of which are confirmed binaries, have been observed with the Australia Telescope Compact Array at 1.4, 2.4, 4.8, and 8.6 GHz. The earliest star cataloged so far, HD 93129A, was also observed at 17.8 and 24.5 GHz. Here we present an analysis of the spectra as well as the structure of the stellar systems. All four spectra show clear evidence of non-thermal emission, indicative of a binary system with a colliding wind region. We discuss the magnetic field of the emitting region of HD 93129A and make predictions on the radiation at high energies. Archive X-ray observations towards the target sources are also investigated and interpreted in the light of the non-thermal emission detected.